Analyzing Water Quality Dynamics Using Multivariate Analysis for a Tidal River in Bangladesh - Quazi Hamidul Bari; Md. Shafiquzzaman; Husnain Haider (Advances in Civil Engineering)
The Bhairab River, characterized by its regular flow and bidaily tidal cycles, is vital to the Khulna region. The River’s water quality is significantly influenced by tidal and seasonal changes. Therefore, comprehensive studies appraising these variations are critically important to fully understand the river’s water dynamics. This research aimed to evaluate the impacts of tidal and seasonal variations on the water quality of the Bhairab River over 1 year. Water samples were collected weekly and hourly from three selected study sites along the river, and physicochemical parameters were analyzed through laboratory testing. The monitored water quality data were analyzed using cluster analysis (CA) and principal component analysis (PCA). Four distinct clusters represent different seasons: premonsoon (PM), postwinter (PW), monsoon (M), and early monsoon and winter (EMW) were identified through CA analysis. The study observed the highest levels of total solids (TS) (13,625–15,950 mg/L), total dissolved solids (TDS) (13,663–14,249 mg/L), chloride (Cl−) (salinity) (6631–7377 mg/L), and electrical conductivity (EC) (8.1–8.6 mS/cm) during the PM period. These concentrations significantly decreased during other periods, reaching their lowest during the monsoon season: TS (800–852 mg/L), TDS (187–193 mg/L), Cl− (32–33 mg/L), and EC (0.33 mS/cm). In contrast, suspended solids (SS) (658–1432 mg/L) and turbidity (320–360 NTU) peaked during the monsoon period and were lower during the PM and PW periods (221–450 mg/L and 120–290 NTU, respectively). PCA highlighted the intrusion of dissolved salts during the PM period, while organic pollutants and SS increased during the early monsoon and monsoon periods. Analysis of 24-h data revealed that TDS and SS levels increased during tidal events and decreased during ebb events. Tide and ebb conditions did not significantly impact dissolved oxygen (DO), Cl−, and conductivity. The comprehensive assessment of water quality variation in the Bhairab River conducted in this study is crucial for ensuring sustainable management of this vital freshwater resource for Khulna, the third largest city in Bangladesh.